IMPLEMENTASI PEMBIASAAN JAMAAH SHOLAT DHUHA DAN SHOLAT DHUHUR UNTUK MENINGKATKAN KARAKTER RELIGIUS DI MI ATTA’AWUN KEDIRI - Ahmad Sihabuddin Mubarok; Muhammad Soni Amrulloh (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
At MI Atta'awun, the practice of Dhuha prayer is held twice a week and dhuhur, on Mondays and Thursdays, in the mosque. Additionally, congregational Dhuha prayers are also conducted in classrooms, using a rotating leadership system among the students. The objective is to instill independence and the ability to correctly recite the Dhuha prayer from an early age. As part of this habit-forming process, students from grades 4 to 6 regularly record their Dhuha prayer performance in journals. The selection of the imam is entrusted to the students, using a rotation system based on seating order or attendance list. This system ensures that each student has the opportunity to lead the prayer and prepare themselves accordingly. The Dhuha prayer is performed separately in each classroom, led by a pre-scheduled student.